Local wisdom-Based Electronic Book on Newton's Law - Sukma, Trisya Afidah; Mundilarto, Mundilarto; Putri, Nadia Darma (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
This study aims to develop a physics e-book based on local wisdom in Newton's law. This research is research and development (R&D) using the 4D model. The stages are: define, design, development, and disseminate. The sampling technique used is the purposive sampling of 36 respondents. At the define, the stage is done with the preliminary analysis, analysis of learners, task analysis, concept analysis, and formulate learning objectives. In the design stage, the arrangement of the instrument, media and format selection, and design of the initial product. The developing stage includes the review by the supervisor, expert assessment, and product trial. The technique of collecting data uses a questionnaire. The questionnaire used in this study was divided into (1) questionnaire on teacher and student needs, (2) product feasibility questionnaire based on material experts and media experts, (3) student response questionnaires. The results of this study show that physics e-book based on local wisdom is very feasible to use in learning physics in Newton's law material. Based on the research result, learning using e-book based on local wisdom is learning media innovation that supports education in the industrial revolution 4.0 without forgetting local culture.